An Examination of Artificial Intelligence in Software Development: Code Generation, Testing, Maintenance, and Security - Rajeshkumar Sudhi (Multidisciplinary Journal of Akseprin Indonesia, 2024)
Artificial Intelligence (AI) is transforming software development by automating critical processes such as code generation, testing, maintenance, and security. AI-driven solutions like OpenAI Codex, GitHub Copilot, and DeepMind AlphaCode are revolutionizing programming by enhancing efficiency, reducing errors, and accelerating development cycles. Similarly, AI-powered testing frameworks improve bug detection, security evaluation, and software performance enhancement. This study analyzes recent advancements in AI-driven software development, assessing its benefits, constraints, and ethical considerations. Additionally, it examines the function of AI in cybersecurity, low-code/no-code development, and workforce transformation. The lecture concludes by discussing potential research directions and the balance between automation and human oversight in AI-augmented software engineering